Exploring Gugon Tuhon Meaning in 'Playing in the Brantas River' as Life Wisdom in Tulungagung - Ari Kurniawan; Yayan Suherlan; Achmad Nur Kholis (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2025)
Traditional culture is often considered outdated in the face of modernization, yet the presence of gugon tuhon in the oral traditions of the Javanese people indicates that local values still hold strong relevance in social life. As a form of local wisdom, gugon tuhon contains various prohibitions and moral messages that have been passed down through generations in the Tulungagung community, serving to protect safety and honor nature and supernatural entities. The prohibition of playing in the river at certain times is one example of gugon tuhon functioning as informal education about safety and harmony with the environment. This study examines the role of visual art as a means of cultural preservation, particularly through the work titled "Playing in the Brantas River." Using a qualitative method with a descriptive-analytical approach, the study collects data through interviews, observations, and documentation. The analysis results show that the visualization of gugon tuhon through painting not only functions as a medium of expression but also as an educational tool for younger generations. This painting presents cultural symbols that remind us of the importance of preserving local wisdom amidst rapid social change.